“I can’t read and don’t understand”: Health literacy and health messaging about folic acid for neural tube defect prevention in a migrant population on the Myanmar-Thailand border - Gilder, M; Moo, P; Hashmi, A; Praisaengdet, N; Wai, K; Pimanpanarak, M; Carrara, V; Angkurawaranon, C; Jiraporncharoen, W; McGready, R (Public Library of Science, 2019)
Health literacy is increasingly recognized as an important determinant of health outcomes, but definition, measurement tools, and interventions are lacking. Conceptual frameworks must include both individual and health-systems domains which, in combination, determine an individual’s health literacy. Validated tools lack applicability in marginalized populations with very low educational levels, such as migrant worker communities on the Myanmar-Thailand border. We undertake a comprehensive health literacy assessment following a case study of a recent public health campaign promoting preconceptual folic acid uptake in this community. A mixed-methods design utilized quantitative analysis of the prevalence and predictors of low Health literacy, and focus group discussions to gather qualitative data from women about proposed and actual posters used in the campaign. Health literacy was measured with a locally developed tool that has been used in surveys of the population since 1995. Health literacy was low, with 194/525 (37.0%) of tested women demonstrating adequate health literacy, despite 63.1% (331/525) self-reporting being literate. Only one third of women had completed 4th grade or above and reported grade level attained in school was more predictive of health literacy than self-reported literacy. Focus group discussions revealed that low literacy, preconceived associations, and traditional health beliefs (individual domain) interacted with complex images, subtle concepts, and taboo images on posters (health-systems domain) to cause widespread misunderstandings of the visuals used in the campaign. The final poster still required explanation for clarity. Low health literacy is prevalent among pregnant women from this migrant community and barriers to communication are significant and complex. Public health posters need piloting prior to implementation as unanticipated misperceptions are common and difficult to overcome. Verbal communication remains a key method of messaging with individuals of low health literacy and educational system strengthening and audiovisual messaging are critical for improvement of health outcomes.